Radiofrequency-targeted vertebral augmentation versus traditional balloon kyphoplasty: radiographic and morphologic outcomes of an ex vivo biomechanical pilot study [Erratum] - Block J (Dove Medical Press, 2013)
Erratum Dalton BE, Kohm AC, Miller LE, Block JE, Poser RD. Clinical Interventions in Aging 2012,7:525–531. In the Disclosure section, Dr Andrew C Kohm is referred to as "AWK". This should be "ACK".Read the original article